Efficacy assessment of PEV2 phage on Galleria mellonella larvae infected with a Pseudomonas aeruginosa dog otitis isolate. (May 2021) - Antoine, C.; Laforêt, F.; Blasdel, B.; Glonti, T.; Kutter, E.; Pirnay, J.P.; Mainil, J.; Delcenserie, V.; Thiry, D.
Abstract: Pseudomonas (P.) aeruginosa is the most frequently isolated Gram-negative bacteria in dog otitis. Antimicrobial resistance is particularly prevalent in P. aeruginosa and phage therapy represents a promising alternative therapeutic strategy. The aim of this study was to assess the efficacy of the PEV2 phage against a clinical P. aeruginosa isolate from a canine otitis using a Galleria (G.) mellonella larvae model. The genomic DNA of PAV237 P. aeruginosa isolate was sequenced and analysed. In a first main experiment, the efficacy of PEV2 phage against PAV237 was assessed at different multiplicities of infection (MOI) (50, 000, 5000, 500, 50) by analyzing the larvae survival rate during 4 days. In a second experiment, the bacterial and phage titer evolutions were assessed depending on two MOIs (50, 000, 5000). No significant survival increase was observed with PEV2 therapy in the infected larvae groups. The generated Kaplan-Meier curves showed that the rate of alive larvae was significantly higher in the non-infected larvae compared to the infected-treated ones irrespective of phage MOIs. An increase of the phage titer was observed at 24 and 48 h post-inoculation (HPI) with both MOIs and the P. aeruginosa titers were lower with MOI 50, 000 and 5000 compared to the infectivity control at 24 and 48 HPI. Even if an ineffectiveness of the PEV2 phage was observed on the larvae survival, PEV2 is active against P. aeruginosa in this model and PEV2 replication is correlated with a lower bacterial proliferation in the phage treated larvae. Highlights: PAV237 is highly virulent for Galleria mellonella larvae. PEV2 phage seems to not improve the survival of the PAV237 infected larvae. Injection of PEV2 phage appears to reduce bacterial replication of PAV237.